(3MGhi GdeNJUQGJ aj GdYed HQHY GdebfWQGJs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3GdeGQOGfj , YHO Gddg Hf Ndjd Hf jhSa Hf YHO Gddg, LeGd GdOjf GdeGQOGfj,J (B809 (3g` s ((3EHQGgje Hf CMeO Hf efUhQ GdTQfhHi s)
(3ChdgG (B:s
(3HYO GdOjHGLI adeG cGf Yde GdhbJ ef CLd GdbQHGJ hCaVd GdWGYGJ s
(3BNQgG (B:s
(3dGjfHZi Cf jYed GdSde ai GdebfWQGJ dGMJjGLg Edi GdLjH s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B53s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B218 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B30 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs